2001
DOI: 10.1037/0033-2909.127.6.715
|View full text |Cite
|
Sign up to set email alerts
|

The effects of child sexual abuse: Comment on Rind, Tromovitch, and Bauserman (1998).

Abstract: B. Rind, P. Tromovitch, and R. Bauserman (1998) examined the long-term effects of childhood sexual abuse (CSA) by meta-analyzing studies of college students. The authors reported that effects "were neither pervasive nor typically intense" and that "men reacted much less negatively than women" (p. 22) and recommended value-neutral reconceptualization of the CSA construct. The current analysis revealed numerous problems in that study that minimized CSA-adjustment relations, including use of a healthy sample, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
4
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(128 citation statements)
references
References 119 publications
(224 reference statements)
4
118
4
2
Order By: Relevance
“…The effect sizes for both young women and men observed in this study were substantially larger than those typically found for the vast majority of more proximate negative life events occurring in adulthood (Aseltine and Kessler 1993;Kessler and McLeod 1984;McLeod and Kessler 1990), which range between a quarter and a third of a standard deviation. Consequently our research informs the debate over the controversial findings of Rind et al (1998) who concluded in a recent meta-analysis that the effect of CSA on young adults' adjustment is actually quite small (e.g., Dallam et al 2001;Ondersma et al 2001;Rind et al 2001). Our study is particularly relevant to this debate because we address two of the principal criticisms of Rind et al's research: that studies using college samples may include only the highest functioning youths experiencing CSA, and that the wide range of abuse definitions found in the metaanalyses have diluted calculations of the impact of traumatic sexual victimization.…”
Section: Discussionmentioning
confidence: 94%
“…The effect sizes for both young women and men observed in this study were substantially larger than those typically found for the vast majority of more proximate negative life events occurring in adulthood (Aseltine and Kessler 1993;Kessler and McLeod 1984;McLeod and Kessler 1990), which range between a quarter and a third of a standard deviation. Consequently our research informs the debate over the controversial findings of Rind et al (1998) who concluded in a recent meta-analysis that the effect of CSA on young adults' adjustment is actually quite small (e.g., Dallam et al 2001;Ondersma et al 2001;Rind et al 2001). Our study is particularly relevant to this debate because we address two of the principal criticisms of Rind et al's research: that studies using college samples may include only the highest functioning youths experiencing CSA, and that the wide range of abuse definitions found in the metaanalyses have diluted calculations of the impact of traumatic sexual victimization.…”
Section: Discussionmentioning
confidence: 94%
“…Some have argued that the traumatic impact of childhood sexual abuse has been overstated (Rind, Tromovitch, & Bauserman, 1998) while others have contended that those experiencing sexual abuse report numerous detrimental effects (Dallam et al, 1998;Paolucci, Genuis, & Violato, 2001). Generally, data derived from clinical samples (Brown & Anderson, 1991;Bryer, Nelson, Miller, & Krol, 1987) suggest high levels of health impairment following sexual abuse while data derived from population studies raise the possibility that many of those experiencing sexual abuse are resilient (Mullen, Martin, Anderson, Romans, & Herbison, 1993) or that the apparent association between abuse and health is attributable to other factors (Rind et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Although early literature reviews concluded that child sexual abuse predicts a range of psychiatric outcomes, 46 more recent meta-analyses based on community samples 7 and college samples 8 suggest that child sexual abuse is weakly associated with later adjustment problems. Unsurprisingly, these findings are controversial 9 , and have been criticized 10,11 and defended 12,13 on several occasions.…”
mentioning
confidence: 99%